DAYA TARIK DAN AKTIVITAS PARIWISATA YANG DIGEMARI WISATAWAN MANCANEGARA DI KELURAHAN UBUD - I Wayan Nurjaya (Soshum: Jurnal Sosial dan Humaniora, 2013)
Attractions and activities of tourism are very important tourism component to attract the tourists come to the tourism area or resort. Since it’s very important role of those tourism components, it needs to know how far is the tourist’ perception on those tourism component above. The aim of this research is to identify foreign tourists attractions and activities at Ubud sub district that they like most. This research uses various approaches such as: social and cultural, social exchange theory and motivation theory. Respondents were taken from foreign tourists Who come from Japan, Australia, America, France, Germany, Holland and British, while the informants were taken from governments and entrepreneurs. Data are taken by observation, interview, questioner and document. The research shows that the tourist attractions in Ubud sub district are liked by the foreigners are views that got the highest appreciation those are 31 respondents (62%), traditional market 30 respondents (60%), temples 27 respondents (54%), Society Friendliness 26 respondent(52%), culture event 24 respondent (48%), so did to the other attractions although got a little appreciations. Tourism activities are also done by the foreigners those are related to fulfillment of physical need such as exercises, hobbies and leisure. It shows that 32 respondents (64%) like walk in the rice field, 29 respondents (56%) like attending culture activities, 26 respondents (52%) like sight-seeing, and the rest choose the other of activities from those are mentioned above. The suggestions taken from this research are: in regarding with the foreigners market is very potential in giving profits to the tourism industry in Ubud, so that it needs to be well preserved, moreover it needs always to be increased in the next period for getting more foreign exchange. The others need to pay more attention are the views and also the patch in he rice field for the foreigner walking on the rice field as it got many appreciations from the foreigners as it mentioned above.